Clonagem e expressão do gene da lectina de Canavalia brasiliensis (ConBr) em Pichia pastoris e Nicotiana tabacum - Carvalho, Cristina Paiva da Silveira (2004)
Cloning and expression of the Canavalia brasiliensis lectin gene were obtained in two heterologous systems: the yeast Pichia pastoris and tobacco plants (Nicotiana tabacum varoXanthi). Six versions of the conbr gene coding for pre-pro-ConBr, pre-ConBr, pro-ConBr, pre-alpha-chain, beta fragment and gama fragment were cloned in Ptchia pastoris GS115 cells. The different inserts were obtained by primers designed frorn the nucleotide sequence of conbr gene (GenBank, access number Y13904). Each insert was subcloned on two different expression vectors, the pPICZaA and pPICZB. The first one allows the recombinant protein to be secreted extracellularly, whereas the second one allows intracellular expression. The transfonned yeast cells with the inserts pro-conbr, pre-conbr, pre-alpha chain and gama fragment were induced to express in the presence of methanol. The lectin expressed from the pre-conbr and pro-conbr inserts, with or without the alpha secretion factor, showed an apparent molecular mass similar to that ofthe native ConBr (30 kDa). These results suggest that rConBr was correctly processed in P. pastoris cells. Extracelular ConBr expression was directed by a secretion alpha factor or by the lectin peptide signal itself. At the second moment of this present research, the conbr gene, with or without the Kozak consensus sequence, was inserted in tobacco plants (Nicottana tabacum varoXanthi) by leaf disc co-culture with Agrobacterium tumefaciens LBA4404 harboring binary plasmids, pBI121::conbr or pBI121::conbrK. The Kozak sequence CACCAUGG was inserted to improve translation of the recombinant protein. The transformation process allowed the selection of tobacco plants expressing the recombinant ConBr with an apparent molecularmass higher than that of the native ConBr. This is the first report of the C. brasiliensis lectin expression in eukariont heterologous systems. Both expression systems constitute important tools for elucidation of the biosynthesis, processing and biological activities of ConBr.